A New Fault-Location Method with High Robustness for Distribution Systems - You, Dahai; Ye, Lei; Yin, Xianggen; Yao, Qiguo; Wang, Ke; Wu, Junchun (Elektronika ir Elektrotechnika, 2013)
This paper proposes a new single-end impedance based fault location method for power distribution systems. Based on direct three-phase circuit analysis, the authors have devised a generalized fault-location formulation in phase domain utilizing the fault admittance matrix. And Newton-Rapson method is used for the solution of fault-locaiton formulation. In order to eliminate the capacitive effect of feeders, the proposed fault location algorithm adopts π model of line for the calculation of voltage and current in iterative process. The validity of the algorithm is tested with IEEE 34 Node Test Feeder using PSCAD-EMTDC. Simulation results have demonstrated that the method has high accuracy and good robustness. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.1896